Innovation in Islam : Traditions and Contributions - Edited by Mehran Kamrava (Berkeley University of California Press, 2011)
Why has the West developed and modernized, while the Muslim world has lagged behind? Why has democracy not found a hospitable home in much of the Muslim world? And why have the opponents of innovation found their message so resonant with ordinary Muslims? This volume offers analyses of the history, causes, and consequences to innovation in Islam.
Include Illustrations and Index.
Traditions and Contributions.
Keywords: Islam -- Islamic fundamentalism -- Islamic renewal